Atenção à saúde nas pequenas e médias empresas de São José dos Campos: estudos de caso - Costa, Denise da Conceição da (2007)
Building actions related to health and safety in small and medium enterprises are not easy tasks, since these enterprises need to deal with poor information, lack of available resources and methodologies developed according to big company characteristics. Based on Case Studies techniques, the present study investigated in four SME not only the way health and safety interventions are carried on, but the reasons why they are conducted that way as well. This investigation made us conclude that lack of available resources, poor information access, the firm culture and management model exert clear influence on the way Heath and Safety actions are conducted. Ergonomics, if conducted in the small firm, will be guided by perception and based on informality, either for changes or measures of the changes. We can conclude that some rules and laws, as well as ergonomic tools, should be developed according to the limitations and needs of the small and medium firms, and so be used to help improve health and safety into them.